Application of ground-penetrating radar in measuring the density of asphalt pavements and its relationship to mechanical properties. Issue Volume 17:Issued 6(2016) (2nd July 2016) - Kassem, Emad; Chowdhury, Arif; Scullion, Tom; Masad, Eyad
Abstract : The ground-penetrating radar (GPR) is a proven technology that is used typically to determine the thicknesses of pavement layers. This paper explores the applicability of the GPR to assess the density of the asphalt layer in pavements. The measurements were conducted on three test sections that were constructed using different asphalt mixtures. Each of the test sections was divided into sub-test sections that were compacted using different compaction methods and number of roller passes in order to achieve a range of asphalt mixture densities. The results showed that there was very good correlation between the GPR results and density of extracted field cores. Consequently, the paper examines the correlation between density and mechanical properties of asphalt mixtures. The results of the mechanical tests provided valuable information on the effect of density on performance.